Development Of Regulations To Prevent And Address Algorithmic Bias In E-Commerce Competition Law - Samon, Siti Nurfadilla; Kasim, Nur Mohamad; Abdussamad, Zamroni (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
The study identified shortcomings in Law No. 5 of 1999 on algorithmic discrimination in the e-commerce business. The study employs normative legal methods, incorporating a legislative, conceptual, and algorithmic justice approach, as well as a comparative analysis of EU and US regulations. Secondary data, including ICC cases, were analyzed through literal, co-curricular, and teleological interpretations. This highlights the limitations of existing norms in addressing digital dynamics. Law No. 5/1999 does not have explicit regulations on automated algorithms, including definitions, transparency, or auditing of systems. Real cases, such as Shopee's internal delivery priority, harm small businesses through biased weighting factors, violating Article 19(d) and Article 25(1)(a). The first step is to mandate that major platforms disclose their algorithmic principles and conduct quarterly independent audits. Furthermore, strengthen ICC with technologists and data management rules. Long-term measures include international cooperation and the application of Pancasila-based ethics to achieve social justice, which is crucial for protecting SMEs in Indonesia's digital market, aligning with the global dominance of algorithms, and in line with ICC's principles aimed at combating AI collusion. Reform promotes healthy and inclusive competition.